2015
DOI: 10.1515/pjvs-2015-0115
|View full text |Cite
|
Sign up to set email alerts
|

A serological and molecular study on the occurrence of mycoplasmas in European bison (Bison bonasus) from two areas of Eastern Poland

Abstract: European bison (Bison bonasus) from two different areas of Eastern Poland showing gross pathology possibly associated with mycoplasma infections were tested for ruminant Mycoplasma species using serological and molecular methods. Fifty-five samples, blood or tissue were collected from 28 animals during 2013-2014. Six sera were positive for Mycoplasma bovis. The ELISA and complement fixation test for Mycoplasma mycoides subsp. mycoides gave a few weak reactions, but were negative by immunoblotting and molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…So far, antibodies against Mycoplasma bovigenitalium have been confirmed in European bison with balanoposthitis [ 33 ]. Previous serological studies have revealed a similar low seroprevalence of M. bovis in European bison [ 4 , 34 ].…”
Section: Discussionmentioning
confidence: 69%
“…So far, antibodies against Mycoplasma bovigenitalium have been confirmed in European bison with balanoposthitis [ 33 ]. Previous serological studies have revealed a similar low seroprevalence of M. bovis in European bison [ 4 , 34 ].…”
Section: Discussionmentioning
confidence: 69%
“…2 Moreover, a study of European bison ( Bison bonasus ) with clinical signs associated with M. bovis found 21% of sampled animals to be seropositive. 7…”
Section: Discussionmentioning
confidence: 99%
“…An M. bovis seroprevalence study of Polish cattle found that clinically healthy cattle had a considerably lower individual seroprevalence than cattle with respiratory disease (16% and 43%, respectively) 2. Moreover, a study of European bison (Bison bonasus) with clinical signs associated with M. bovis found 21% of sampled animals to be seropositive 7.…”
mentioning
confidence: 99%
“…Bison can be infected with M. bovis (18). Previously, six sera with specific antibodies to M. bovis were found in European bison (Bison bonasus) which came from Eastern Poland and had gross lung lesions typical of M. bovis infection (6). Cervids have been reported to be infected with haemoplasmas (10), M. bovis (7), M. agalactiae (2), M. conjunctivae (8), and Mccp (1).…”
Section: Discussionmentioning
confidence: 99%